Artemisinin from minor to major ingredient in Artemisia annua cultivated in Egypt - El-Moataz Bellah El-Naggar, Mohamed Azazi, Emil Švajdlenka, Milan Å½emliÄka (Journal of Applied Pharmaceutical Science, 2013)
Artemisia annua is currently the only source for the commercial pharmaceutical production of artemisinin as neither its chemical synthesis nor its in vitro production is economically feasible. However, the very low amount of artemisinin in Artemisia annua L., (0.01-0.6%) of dry weight has made artemisinin-based drugs remains expensive and is hardly available on a global scale. Limitations in the supply of this promising and most potent antimalarial compound makes the cultivation of this plant is still the only valid source to satisfy the high demands and the vast need of artemisinin at a reduced acceptable market price for most patients. In this paper we attempted to increase the cultivating area of this important plant by cultivating A.annua seeds for the first time in the western desert of Egypt to improve its agricultural yields in order to ensure a steady global supply of artemisinin and to study the environmental impact of the cultivation area on the amount of artemisinin production. The high artemisinin concentration reported in this study (4.85-4.90%) of dry weight has identified the Egyptian desert for the first time as a new promising cultivating area for pharmaceutical production of artemisinin. A very simple method was developed using liquid chromatography tandem mass spectrometry (LC-MS/MS) for the quantification of artemisinin in both plant material and pure samples
Keywords: Artemisia annua, artemisinin, El